Implementasi Program Pemberian Makanan Tambahan dalam Mendukung Upaya Pencegahan Stunting - Novianto, Eko Deddy; Suprapto, Sentot Imam; Sujatmi, Melli Maria br Limbong (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The Supplementary Feeding Program Pemberian Makanan Tambahan (PMT) Genting is a local food–based health initiative aimed at supporting stunting prevention efforts. The program emphasizes the use of affordable and nutritious local ingredients to improve child nutritional status through community participation. Objective: The purpose of this service was to increase public knowledge and awareness about the importance of the local-based Pemberian Makanan Tambahan program and to encourage the utilization of local nutritious food ingredients as an effort to accelerate stunting prevention. Method: This public service was conducted using a community-based intervention approach involving 40 mothers with children aged 6–59 months at Posyandu Golf, Guntung Payung. Activities included educational sessions, local food preparation demonstrations, and evaluation through pre- and post-tests to measure changes in knowledge levels. Result: The results showed an increase in mothers’ knowledge regarding PMT. Before the intervention, 37.5% of respondents had good knowledge, which increased to 55% after the activity. This indicates that community education effectively enhances mothers’ understanding of local food utilization for stunting prevention. Conclusion: The implementation of the local-based PMT program at Guntung Payung Health Center successfully improved community knowledge and supported stunting prevention efforts through education and local food empowerment.